Oral exposure to aluminum chloride for 28 days suppresses neural stem cell proliferation and increases mature granule cells in adult hippocampal neurogenesis of young‐adult rats. Issue 8 (20th February 2022) - Shimizu, Saori; Maeda, Natsuno; Takahashi, Yasunori; Uomoto, Suzuka; Takesue, Keisuke; Ojiro, Ryota; Tang, Qian; Ozawa, Shunsuke; Okano, Hiromu; Takashima, Kazumi; Woo, Gye‐Hyeong; Yoshida, Toshinori; et al.
Abstract: Aluminum (Al), a common light metal, affects the developing nervous system. Developmental exposure to Al chloride (AlCl3 ) induces aberrant neurogenesis by targeting neural stem cells (NSCs) and/or neural progenitor cells (NPCs) in the dentate gyrus (DG) of rats and mice. To investigate whether hippocampal neurogenesis is similarly affected by AlCl3 exposure in a general toxicity study, AlCl3 was orally administered to 5‐week‐old Sprague Dawley rats at dosages of 0, 4000, or 8000 ppm in drinking water for 28 days. AlCl3 downregulated Sox2 transcript level in the DG at the highest dosage and produced a dose‐dependent decrease of SOX2 + cells without altering numbers of GFAP + or TBR2 + cells in the subgranular zone, suggesting that AlCl3 decreases Type 2a NPCs. High‐dose exposure downregulated Pcna, upregulated Pvalb, and altered expression of genes suggestive of oxidative stress induction (upregulation of Nos2 and downregulation of antioxidant enzyme genes), indicating suppressed proliferation and differentiation of Type 1 NSCs. AlCl3 doses also increased mature granule cells in the DG. Upregulation of Reln may have contributed to an increase of granule cells to compensate for the decrease of Type 2a NPCs. Moreover, upregulation of Calb2, Gria2, Mapk3, and Tgfb3, as well as increased numbers of activated astrocytes in the DG hilus, may represent ameliorating responses against suppressed neurogenesis. These results suggest that 28‐day exposure of young‐adult rats to AlCl3 differentially targeted NPCs and mature granule cells in hippocampal neurogenesis, yielding a different pattern of disrupted neurogenesis from developmental exposure. Abstract : We previously showed that developmental exposure to aluminum chloride (AlCl3 ) disrupted hippocampal neurogenesis in rats and mice. The present study investigated whether hippocampal neurogenesis is similarly affected by AlCl3 exposure in a general toxicity study using young‐adult rats. AlCl3 exposure for 28 days decreased Type 2a NPCs but increased mature granule cells through multiple mechanisms, suggesting that AlCl3 differentially targeted NPCs and mature granule cells in hippocampal neurogenesis to generate different patterns of disruption from developmental exposure.